Unexpected Rapid Increase in the Burden of NAFLD in China From 2008 to 2018: A Systematic Review and Meta‐Analysis - Zhou, Feng; Zhou, Jianghua; Wang, Wenxin; Zhang, Xiao‐Jing; Ji, Yan‐Xiao; Zhang, Peng; She, Zhi‐Gang; Zhu, Lihua; Cai, Jingjing; Li, Hongliang (Hepatology (Baltimore, Md.), 2019)
With rapid lifestyle transitions, the increasing burden of nonalcoholic fatty liver disease (NAFLD) in China has emerged as a major public health issue. To obtain a comprehensive overview of the status of NAFLD over the past decade, we evaluated the epidemiology, risk factors, complications, and management of NAFLD in China through a systematic review and meta‐analysis. Five English literature databases and three Chinese databases were searched for relevant topics from 2008 to 2018. A total of 392 studies with a population of 2,054,554 were included. National prevalence of NAFLD was 29.2%, with a heavier disease burden among the middle‐aged, males, those in northwest China and Taiwan, regions with a gross domestic product per capita greater than 100,000 yuan, and Uygur and Hui ethnic groups. Currently, original studies on natural history and complications of NAFLD in China are scarce. Several studies revealed that NAFLD is positively correlated with the incidence of extrahepatic tumors, diabetes, cardiovascular disease and metabolic syndrome. The Chinese population may have a higher hereditary risk of NAFLD due to more frequent nonsynonymous mutations in genes regulating lipid metabolism. Ultrasonography is the primary imaging tool in the detection of NAFLD in China. Serum tests and risk stratification algorithms for staging NAFLD remain under investigation. Specific pharmaceutical treatments for NAFLD are still undergoing clinical trials. It is noteworthy that the Chinese are underrepresented compared with their proportion of the NAFLD population in such trials. Conclusion: China experienced an unexpected rapid increase in the burden of NAFLD over a short period. Rising awareness and urgent actions need to be taken in order to control the NAFLD pandemic in China.